Optimizing the Development of Kampung Perca in Bogor City Through Improving The Governance System, Increasing Resources and Utilizing Technology: Optimalisasi Pengembangan Kampung Perca Kota Bogor Melalui Perbaikan Sistem Tata Kelola, Peningkatan Sumber Daya dan Pemanfaatan Teknologi - Sutarti; Nani Cahyani; Ani Mekaniwati; Dwi Maulina; Febriana Indah Lestari; Intan Permatasari; Michael M. Ruswan; Tubagus AC. Fikri; Accasia Miranda Leva (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
MSMEs play an essential role in the expansion of the Indonesian economy, covering 99% of all business entities. Regarding employment, MSMEs contribute 60.5% to GDP and 96.9% of all national work. Even though they have demonstrated the importance of their role in the national economy, micro, small, and medium enterprises (MSMEs) continue to need help to face various challenges. Perca villages also face challenges related to three aspects, namely organizational management/governance, resources, and marketing. Therefore, the IBIK PkM Team tries to provide the following solutions: 1) conducting training and assisting in developing organizational management policies, 2) training and simulations on designing a financial reporting system based on SAK EMKM, 3) training or training related to entrepreneurship and marketing strategies, 4) sewing training to improve mothers' skills, 5) training, mentoring, and product marketing simulations using technology, design/creation of the Kampung Perca website and marketing models on social media. This service has succeeded in achieving its goals and has brought positive changes to Perca Village, namely the formation of governance guidelines in partner organizations as well as a simple financial management recording system for partner organizations, increased understanding of trustees and administrators regarding asset and capital management, increased entrepreneurial spirit, increased understanding regarding marketing strategy by utilizing digital technology and increasing the expertise of member mothers in sewing clothes, creating the eeb and other digital features (social media) to develop the marketing of partner member business products.